Narrativas do design em livros digitais: experiência de leitura e compreensão literal do usuário infantil da geração alpha - LIMA, Thaís Lemos (2020)
Considering the multimedia possibilities and sensory stimuli that digital children's books can have, it is important to think of these resources as narrative elements, that is, that complement, repeat or add meaning to the central plot. However, interactive multimedia resources do not always contribute effectively to the reader’s comprehension of the history. So that, this research makes a Case Study, using three books from the children's reading application TecTeca, focusing on the investigation of the level of literal understanding of the content that the user-reader, of Generation Alpha, can obtain after reading. Thus, in the definition of the research subjects referring to the Alpha Generation, there was the voluntary participation of 24 children between six and ten years old, held in three different institutions: three groups of three children in School 1 (private), three groups of two children at School 2 (private), and three groups of three children at School 3 (public). With that in mind, checklists, user observation, focus groups and a sensitive creative method were used to obtain qualitative and quantitative data to assess the level of comprehension of these participants. The main results found validate this relationship between digital book design narratives and children's perceptions of history. Finally, recommendations are made to improve the performance of the digital books evaluated, in the TecTeca application.